Virtual legenda - Kilhof, Markéta (Vysoké učení technické v Brně. Fakulta výtvarných umění)
Předmětem práce je voda. Intermediální instalace tvořená objekty a videem.

The main topic of the work is water. Intermedial installation consisting of objects and video.
Virtual Legend
Keywords: Virtual Legenda; video; instalace; voda; Virtual Legenda; video; installation; water